Sequential English Auctions: A Theory of Opening-bid Fishing - Joseph Uri Podwol (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2015)
Cassady (1967) describes an auction in which the auctioneer "fishes" for an opening bid, calling out lower and lower amounts until an opening bid is eventually placed. Once a bid is placed, it is not uncommon for the bidding to escalate above the initial starting price. The current study explains this puzzle in a model in which an auctioneer sells an indivisible good via English ascending-price auction and cannot commit to keeping the item off the market should the initial starting price fail to elicit any bids. A key insight of the paper is that the well-known strategy equivalence between the English auction and the second-price auction fails to extend to the sequential setting. This difference has important implications for the equilibrium starting-price path, giving rise to a Coase conjecture in the English auction but not in the second-price auction.
Keywords: 330